(untitled) (International Journal of Scientific Trends, 2024)
This article examines the issues of spirituality using the example of ethnic traditions, focusing on national and universal values, the preservation of traditions and traditions, the education system, assessing the standard of living of families, improving the well-being of residents and focusing on ethnic traditions in the field of spirituality and education when analyzing the current state.